Colombia : The Economic Foundation of Peace - Giugale, Marcelo M.; Lafourcade, Olivier; Luff, Connie (Washington, DC: World Bank, 2013)
The book intends to trigger, and support policy debate in Colombia. The first part distills four thematic chapters, responsive to the country's current realities, as well as to the five decades of development partnership with the Bank, spanning the entire development spectrum. First, violence, sustainable peace, and development introduces the reader to the source of violence - armed, and social conflicts, and drug trade prevalent in the country - to form a framework of understanding on the economic, and social costs for building peace, and enable sustainable growth. Second, such growth is examined within the macroeconomic, and fiscal framework, to ensure a healthy financial system, and create a business environment to foster private sector development. Third, such eventual success, drives us through Colombia's traditional socioeconomic progress, though through its recent setbacks as well - economic recession, increased macroeconomic instability, and judicial uncertainty - all eroding potential welfare gains. Fourth, and ultimately, the demand for governance and quality of government reveals the coexisting problems faced by strong and weak governance, and explores a strengthened governance based on selectivity and gradualism in building high quality government. To support this analysis, the second part, provides sector-specific realities, including its fiscal framework, public debt management, financial sector and pension reform. The development agenda calls for a government to reach a higher growth plateau, allowing a chance for sharing in that growth, and making the state an icon of quality.